Systematic Literature review on the Use of Applications of Smartphones for Teaching English in EFL Contexts - Prodhan Mahbub Ibna Seraj; ABM Rahmatullah (UNIB Press, 2022)
This review paper provides an overview of the use of applications of smartphones, target language skills, methodology, and EFL contexts from the studies published between 2010 and January 2020. As per time frame and parameters followed by the PRISMA model, 45 of 2707 studies were retrieved from four reputable online databases, namely Springer link, Web of Science, Scopus, and ScienceDirect, were eligible for this study, All these studies (n=45) scrutinized and analyzed with NVIVO-12 for obtaining the objectives of this study. The findings showed that 25 applications of smartphones were employed, and the most used application was Short Message Service (SMS). Further, the findings reported that vocabulary was the most targeted language skills, the quantitative research methodology was the most popular and highest number of studies held in Iran employing smartphone apps in ELT. Based on the findings, the study would provide some implications and suggestions over the use of the applications of smartphones for facilitating teaching and learning language skills in the EFL contexts for educators and researchers.